A rare cause of primary amenorrhoea, the XY female with gonadal dysgenesis. (9th February 2015) - Mannaerts, Dominique; Muys, Joke; Blaumeiser, Bettina; Jacquemyn, Yves
Abstract : Disorders of sexual development are conditions where sexual phenotype and genotype are discordant. Genetic sex is determined at conception as the ovum is fertilised by a spermatozoon that contains either an X or Y chromosome. A complex pathway determined by genes and hormones leads to gonadal differentiation into testis or ovary and promotes the development of internal and external genitalia. We present a case of an 18-year-old woman who presented with primary amenorrhoea. She was a virgin, and apart from hirsutism and overweight, had no complaints. Her family history was insignificant. The patient was tall and had underdeveloped breasts. Her blood results showed hypergonadotropic hypogonadism. A 46, XY genotype was detected with karyotype analysis. Ultrasound and MRI demonstrated the presence of a uterus, but no overt gonads. Laparoscopy was performed, with bilateral removal of streak ovaries.